Early Childhood Numeracy Skill Assessment: A Preparation Study For Elementary School Transition - Nurul Kusuma Dewi; Adriani Rahma Pudyaningtyas; Vera Sholeha; Anayanti Rahmawati; Warananingtyas Palupi; Muhammad Munif Syamsuddin (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Low numeracy skills in early childhood affect primary school readiness. Children will have difficulty facing challenges in mathematics, problem solving, other subjects, daily activities, self-confidence, motivation to learn, and social interaction. This study aims to analyze the level of numeracy skills of children aged 5-6 years in the Surakarta Residential and identify aspects of numeracy skills that are still low, so that it can be a reference in providing appropriate stimulation. The research method used a survey. Data collection techniques through a numeracy assessment questionnaire and validated by expert judgment. The sampling technique used convenience sampling by randomly selecting two kindergartens in each district / city in Surakarta Prefecture, so that 386 respondents of children aged 5-6 years were obtained. The data were analyzed using descriptive statistics. The results showed that 13.2% of the children had high numeracy skills, 67.9% were in the medium category, and 18.9% were in the low category. Of the five aspects of numeracy measured (number, geometry, measurement, computation, and data analysis), the number aspect was found to be the most mastered by the children. The geometry, measurement, and computation aspects were in the moderate category. The data analysis aspect showed the lowest results, indicating difficulties in understanding more complex numerical concepts. These findings suggest the need for more innovative and inquiry-based learning strategies to improve children's numeracy skills. The research recommendations emphasize the importance of strengthening activity-based learning methods, using interactive teaching aids, and increasing the involvement of teachers and parents in supporting early numeracy skills.